1867 Ariz. Sess. Laws 22, An Act To Prevent The Improper Use Of Deadly Weapons And The Indiscriminate Use Of Firearms In The Towns And Villages Of The Territory, § 2 - (:unkn) unknown (General Publisher, 1867)
Prohibited the indiscriminate discharge of any carried pistol or gun in the public streets or highways. Violators fined not less than ten nor more than fifty dollars and imprisoned not less than two nor more than ten days in the county jail, as well as costs of prosecution.
--
Keywords: DISCHARGE